2011
DOI: 10.2320/matertrans.l-mz201108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zn-Based Alloys Coating on Mechanical Properties and Interfacial Microstructures of Steel/Aluminum Alloy Dissimilar Metals Joints Using Resistance Spot Welding

Abstract: The effects of Zn-based alloys coating (Zn, Al-Zn and Al-Mg-Zn) on the bondability of steel/aluminum alloy dissimilar metals joints were evaluated, in order to achieve strength in lower welding current. In the joint with Zn-based alloys insert, the oxide film on the aluminum alloy was sufficiently removed through eutectic reaction of Zn-based alloys and aluminum. In the joint with Zn-coated steel (GI), higher welding current is necessary to discharge the zinc coating and the oxide film from the bonding interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 6 publications
0
17
0
1
Order By: Relevance
“…By referring to the Al-Zn binary phase diagram coupled with the EDS point and line scan results, the interface diffusion layer formed was a eutectic layer consisting of solid solution of Al and Zn, where slightly more Zn could be present in the Al solid solution, while only very limited Al could be existent in the Zn solid solution at room temperature. 42 Patel et al 20 in the USW of Al 5754-O to HSLA steel and Ueda et al 43 in the RSW of Al to galvanized steel also observed the formation of Al-Zn eutectic structure at the weld interface.…”
Section: Resultsmentioning
confidence: 88%
“…By referring to the Al-Zn binary phase diagram coupled with the EDS point and line scan results, the interface diffusion layer formed was a eutectic layer consisting of solid solution of Al and Zn, where slightly more Zn could be present in the Al solid solution, while only very limited Al could be existent in the Zn solid solution at room temperature. 42 Patel et al 20 in the USW of Al 5754-O to HSLA steel and Ueda et al 43 in the RSW of Al to galvanized steel also observed the formation of Al-Zn eutectic structure at the weld interface.…”
Section: Resultsmentioning
confidence: 88%
“…The welding time can then control the resulting intermetallic layer thickness. Ueda, et al [256] furthered this work with higher strengths at lower currents using Al-Mg-Zn coated steels. This coating melts at a lower temperature than Zn and Al-Zn coatings but is still able to remove the coating and oxide layer sufficiently through expulsion of the eutectic reaction products.…”
Section: Resistance Spot Weldingmentioning
confidence: 88%
“…Another method to impact the heat imbalance between the Al and steel is through manipulation of electrode materials or geometries. There is limited information published, though most welding Al directly to steel use a matching pair of F-type rounded electrodes with dome radius 40 mm and a face diameter of 6 mm [55,181,256,257]. Truncated, 458 cone with a 8 mm face diameter has also been noted [166].…”
Section: Resistance Spot Weldingmentioning
confidence: 99%
“…Liu et al [92] in the hybrid laser-TIG welding of Mg-to-steel have used Sn as an interlayer and showed the improvement of the mechanical properties. [102] have used Zn coated steel to minimize the reaction between Al and Fe during the welding and showed the improvement of the mechanical properties.…”
Section: Welding Of Dissimilar Mg-to-steel Alloysmentioning
confidence: 99%